Power in powerlessness : a study of Pentecostal life worlds in urban Chile - Lindhardt, Martin. (Religion in the Americas, 2012)
Exploring the ritual and everyday religious practices through which Pentecostal life worlds unfold this book breaks new ground in the study of Latin American and global Pentecostalism. In addition to asking the familiar question of why many lower class Latin Americans convert to Pentecostalism, the author asks another question, so far largely neglected in the scholarly literature: how, or through what processes, do people begin and continue to relate to themselves and the social world in a particular Pentecostal way? For members of the Evangelical Pentecostal Church in Valparaíso, Chile, life is pervaded by divine and satanic presence and intervention. Through its fine grained analysis of different ritual, discursive/narrative and reflective processes the book shows how church members integrate sacred others into their everyday lives - or how they learn to live, think and behave as Pentecostals.